Bridge launching - Rosignoli, Marco (Thomas Telford, 2002)
Devoted to bridges that are built by incremental launching methods, using prestressed composite materials, this handbook integrates the static, aesthetic, and economic aspects of construction techniques for building these state-of-the-art structures.